Happy pets shop / Vianney Siging... [et al.] - Siging, Vianney; Julius, Florence; Geluing, Ellisra; Johndary, Mohd Alfazzi (Faculty of Applied Sciences, 2014)
Happy Pet Shop is being established in 11 March 2015. It is the first company in Borneo that concern about the pet's needs and comfort it is being located in Ranau town, Sabah. Our main company is also located at Ranau town, Sabah. Our company's vision is to be the most well-known pet shop on the state. Happy Pet Shop is also come out with our own mission. Our first mission is to be the best pet shop in Ranau for five years. Other than that, to gives the best customer service than others store. Last but not least, become the customer's first choice pet store. Our company's objective is to fulfil the satisfaction, needs and wants of the customer. In order for us to nm with our business, we never neglect our own surroundings and even for our own environments. Our products come from the best quality that safe to be used for pets and human. We put the customers' pets comfort and needs at the first class as we give the best service in town.